La clarté de la loi obscurcie par le technicisme formel de son écriture - Hervé Moysan (Lingue Culture Mediazioni, 2020)
Clarity in legal drafting must be considered not only in terms of the writing itself (style, technicality of language, etc.) but also in relation to the structuring of legislative and regulatory provisions. The vast majority of laws and regulations adopted today amend existing texts, often in “surgical” fashion, rather than creating new ones. The way in which such amendments are drafted and structured renders them barely meaningful, insofar as they do not, in themselves, enable us to ascertain the state of the law. There is manifestly considerable room for improvement in legislative drafting techniques. Several possible models could be adopted to achieve significant progress in clarity. The stance taken by the French Council of State in its 2016 annual study on the simplification and quality of the law is, therefore, a surprising one. It rules out any changes to drafting techniques, except at the margins in relation to the pathological case of provisions pertaining to overseas departments and territories.